Mechanical Properties of Deep Variable Dip Joint Rock Mass in Reservoir Area under Wet and Dry Conditions - Fei Li; Huafeng Deng; Wenwen Liu; Guoyong Duan (Advances in Materials Science and Engineering)
The mechanical property of deep complex jointed rock mass is a hot topic in rock mechanics. In order to grasp the deformation and damage rules of through-going variable dip joint rock masses, the triaxial compression test and joint surface morphology scan test were conducted on cylindrical specimens in dry and wet conditions under 0, 5, 10, and 20 MPa water pressure. Through these tests, the deterioration law of rock samples under different pore water pressure in dry and wet conditions was studied. The effect of pore water pressure on the strength of saturated jointed rock sample is nonlinear. The imposed pore water pressure can significantly increase the axial deformation of rock samples, and higher pore water pressure can facilitate the deformation deterioration of samples. When the pore pressure is high, the rock samples show the characteristics of sliding shear failure. Under different pore pressure, the compressive strength of dry jointed rock is significantly higher than that of saturated jointed rock, and the saturated rock is more susceptible to sliding in the joint plane than dry rock. Dry jointed rock samples have stronger deformation ability than saturated jointed rock samples. The change rate of the morphologic parameters and the distribution of the failure cracks indicate that the stress concentration is evident in the middle of the joint plane.